Augustan marriage laws in Augustan Inscriptions: Signs of Persuasion? - Ching-Yuan Wu (Classical Association Annual Conference, 2023)
As curator of laws and morals (curator legum et morum), a charge bestowed by the Senate and the Roman people on three separate occasions (19 BCE, 18 BCE, 11 BCE, cf. RGDA 6, Dio Cass. 54.30.1, Suet. Aug. 27), Augustus legislated marriage, using the mos maiorum as guidance for a new Roman society that was his to fashion (RGDA 8; Eck 2022). The Lex Iulia de maritandis ordinibus (LIMO) of 18 BCE became a centerpiece legislation with socio-politically comprehensive and enduring impact, leading to subsequent legislative interventions on the Roman institution of marriage from the Augustan period down to the Age of Constantine (Treggiari 1991, 13-36; Grubbs 1993). In some interpretations, the legislative interventions of marriage effectively "collapsed" Roman private life (Raditsa 1980), merging it with a new Roman state apparatus that "officially made proper family behavior part of a citizen's duty," including the obligation "to marry and procreate in a chaste and respectable manner" (Severy 2003, 55). Legislating marriage was effectively a social engineering project (Dolganov 2022), and not without risks to the legislators. Direct evidence of opposition can be found in historial and biographical accounts, and the equestrian order was particularly vocal (Suet. Aug. 34; Dio Cass. 56.4-10). Recently, Warner Eck's study on the commentarius of 5 CE integrated into the Lex Troesmensium provided convincing evidence that significant socio-political resistance against legislative intervention forced Augustus to retract a commentarius of 5 CE which the Lex Papia Poppaea of 9 CE was based upon (ex quo lex P(apia) P(oppaea) lata est), though with noticeable differences in the numbering of chapters (Eck 2022, 2019, 2016). Eck also made the interesting observation that known resistance efforts were not necessarily direct public agitation, but rather could be described as "ingenious attempts" (ingeniöse Versuche) to frustruate the utility of the legislation (Eck 2022, 73). The observation highlights the potentially simplistic approach in describing the range of reactions and counter-reactions associated with Augustan marriage laws as resistance and counter-resistance. The difficulty in taking this approach to study complexities in the range of responses towards the legislating of marriage lies in the availability of sources and the quality of those available. Shades of commentary and other complex reflections on Augustan marriage legislations – for example Horace's Carmina of 23 BCE (C. 3.6, 3.24) and 13 BCE (C. 4.15), Propertius's elegies of 28 BCE (2.7) and 18 BCE (4.11), and Ovid's Ars Amatoria of 2 CE, the latter of which has recently received particular treatment (Hutchinson 2017) – can be elicited from Augustan literary evidence, but hardly straightforward firsthand reports. Historical and biographical accounts may be vivid, as those from Cassius Dio's (54.16; 56.1-10) and to a lesser extent Suetonius (Suet. Aug. 34) and Tacitus (Ann. 3.25-28), but much more removed from immediate context. To extend the scope of discovery, this paper asks what other Augustan inscriptions can inform us on the shades of reactions in the Augustan period. Inscribed texts were more than verbatim transcriptions of documents produced in response to and within the context of social movements. The act of inscribing and setting up were performative aspects of immediate socio-political importance, acting as the legislator/reformer's attempt to impress and opress on the one hand, and responses from those who can afford to engage in a public and formal dialogue regarding an issue.  This paper argues that the performative acts seen on inscribed texts in the Augustan period that specifically respond to marriage legislation or the institution of marriage ought to be understood as persuasive acts. Two inscriptions are discussed in this paper: the SC de ludis saecularibus of 17 BCE and the so-called Laudatio Turiae of 8 CE. Hugh Lindsay (2009) and Josaiah Osgood (2014) focused on aspects of social response regarding the latter, and Warner Eck (2019) has highlighted social resistance regarding the former. This paper seeks to combine the two strands of study on two inscriptions that seem to speak to Roman audiences with deeply entrenched positions on the question of legislating marriage, and read them as attempts of persuasion, both to convey the concerns of their respective parties and impressing upon their respective oppositions on the importance of their approaches toward social order under the curator legum et morum.